Ethical and metaphysical foundations of the rejection of determinism by Aquinas - Dudley, John (Verbum – Analecta Neolatina, 2004)
In this article, an attempt is made to show how freedom is possible. The objection that Divine Providence and its opposite, scientific or physical determinism, make freedom impossible is examined. The question is raised as to whether the universe consists of things (beings/substances), which is a presupposition of scientific determinism. The order in the universe is held not to be an objection to freedom. It is argued that the future is not determined on the basis that causes refer to the past, not the future. Freedom would appear to depend on the soul not being determined like a stone, but a self-mover. In addition, intellect appears necessary, since freedom requires choice, which in turn requires the capacity to deliberate. If both soul and intellect are required for freedom, it is understandable that human beings alone in the universe are free.